Modulating Th2 Cell Immunity for the Treatment of Asthma - León, Beatriz; Ballesteros-Tato, Andre (Frontiers in Immunology, 2021)
It is estimated that more than 339 million people worldwide suffer from asthma. The leading cause of asthma development is the breakdown of immune tolerance to inhaled allergens, prompting the immune system's aberrant activation. During the early phase, also known as the sensitization phase, allergen-specific T cells are activated and become central players in orchestrating the subsequent development of allergic asthma following secondary exposure to the same allergens. It is well-established that allergen-specific T helper 2 (Th2) cells play central roles in developing allergic asthma. As such, 80% of children and 60% of adult asthma cases are linked to an unwarranted Th2 cell response against respiratory allergens. Thus, targeting essential components of Th2-type inflammation using neutralizing antibodies against key Th2 modulators has recently become an attractive option for asthmatic patients with moderate to severe symptoms. In addition to directly targeting Th2 mediators, allergen immunotherapy, also known as desensitization, is focused on redirecting the allergen-specific T cells response from a Th2-type profile to a tolerogenic one. This review highlights the current understanding of the heterogeneity of the Th2 cell compartment, their contribution to allergen-induced airway inflammation, and the therapies targeting the Th2 cell pathway in asthma. Further, we discuss available new leads for successful targeting pulmonary Th2 cell responses for future therapeutics.